Analysis of Pump Agrigarts Electric Power Control Elements in the Supply of Multi-Storey Houses Water Supply - Islom Khafizov; Komil Gafforov; Imomova Zilola (Research Parks Publishers, 2021)
Today, the world's rapid population growth is leading to an increase in people's need for food and the resources they need to live. In particular, the excess of the demand for drinking water allows us to use it wisely without wasting it. controlling the pressures in the water pipes through optimal control of the connection, aimed at preventing excessive losses.